Lipid profiling of healthy and Alzheimer's‐affected mouse brains by using DESI imaging mass spectrometry: How lipid dyshomeostasis can contribute to Alzheimer's disease: Developing topics. (7th December 2020) - Lazarian, Artur; Menon, Vilas; Fowler, Brandon; McIntire, Laura Beth
Abstract: Background: Alzheimer's disease (AD) is one of the biggest health challenges that we face worldwide, which causes millions of deaths annually and costs reach many billions. Yet, the cause of the disease is not fully understood and therefore no effective treatment is available up to date. Lipidomic data from autopsy brain, human plasma and animal models highlights severe lipid dyshomeostasis in AD. Thus, the disruption of lipid metabolism and the homeostasis are thought to play a crucial role in the development of Alzheimer's pathology. The importance of lipid metabolism in AD is supported by GWAS studies which have identified multiple lipid modifying enzymes and interacting proteins. It is likely then that specific pathways in lipid metabolism underlie AD disease mechanisms leading to behavioral impairment. Specifically, previous studies have shown that the loss of polyunsaturated fatty acids among multiple phospholipid classes is common in AD affected human brain and mouse models. Method: Therefore, it's of high importance to screen the lipid species in both healthy and AD affected human and mouse brains. By applying Mass Spectrometry (Synapt G2‐Si), we aim at setting up a workflow for high‐throughput quantitative and qualitative lipidomics profiling for healthy and AD affected brains. Result: Here, we show the phylogenetic comparisons of genes and their SNPs that were found by GWAS studies to be risk factors in AD. These SNPs in humans were compared to that of primates and other animals. In addition, preliminary Mass Spectrometry runs were carried out for setting up a lipid screening workflow. Conclusion: As supported by our preliminary data, the MS will allow us to detect broad range of versatile lipid species by applying targeted and untargeted analysis, Ion Mobility Separation, and DESI Imaging.